2008
DOI: 10.1029/2007jd009754
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous reactions of methacrolein and methyl vinyl ketone: Kinetics and mechanisms of uptake and ozonolysis on silicon dioxide

Abstract: [1] Methacrolein (MAC) and methyl vinyl ketone (MVK), two major first-generation products in the oxidation of isoprene, play important roles in tropospheric chemistry. However, little is known about their heterogeneous fate. Here we investigated the heterogeneous reactions of MAC and MVK on particles of silicon dioxide (SiO 2 ), the major constituent of mineral dust in the troposphere, under simulated tropospheric conditions. We first investigated the adsorption and desorption processes. It was found that MAC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 84 publications
0
37
0
Order By: Relevance
“…Nighttime is usually more humid than daytime, increasing the significance of aqueous-phase and heterogeneous reactions. Recent laboratory studies have suggested that H 2 O 2 and ROOH could also be produced during aqueous-phase reactions and heterogeneous reactions on particles [Chen et al, 2008a[Chen et al, , 2008bZhang et al, 2009]. On 25 July concentrations of C 2 -C 11 alkenes decreased from 4.5 to 3.3 ppbv during 1800-2000, which is when the peroxides accumulated.…”
Section: Nighttime Production Of Peroxidesmentioning
confidence: 99%
“…Nighttime is usually more humid than daytime, increasing the significance of aqueous-phase and heterogeneous reactions. Recent laboratory studies have suggested that H 2 O 2 and ROOH could also be produced during aqueous-phase reactions and heterogeneous reactions on particles [Chen et al, 2008a[Chen et al, , 2008bZhang et al, 2009]. On 25 July concentrations of C 2 -C 11 alkenes decreased from 4.5 to 3.3 ppbv during 1800-2000, which is when the peroxides accumulated.…”
Section: Nighttime Production Of Peroxidesmentioning
confidence: 99%
“…The details of the sample processing and analysis are described in our previous work. [50][51][52] Blanks were sampled and analysed using the same method before the reaction.…”
Section: Instrumentation and Methodsmentioning
confidence: 99%
“…Methacrolein (MACR) and methyl vinyl ketone (MVK), as two major first-generation products in the oxidation of isoprene, are of great interest due to their large global abundance (Montzka et al, 1993;Griffin et al, 1999;Simpson et al, 1999) and high reactivity (Gierczak et al, 1997;Chen et al, 2008b). The atmospheric transformation of these two carbonyls has received considerable studies, mainly including determining their gas-phase reaction products Atkinson, 1989, 1990;Aschmann et al, 1996;Orlando et al, 1999), measuring aerosol growth from their photooxidation Ng et al, 2006), elucidating reaction pathways in terms of SOA formation (Kroll et al, 2005;Surratt et al, 2006;Szmigielski et al 2007), and investigating their uptake kinetics onto particles (Nozière et al, 2006;Chen et al, 2008a;Zhao et al, 2010). Chamber experiments have demonstrated that MACR is an important intermediate in SOA formation whereas MVK was found to produce no SOA Surratt et al, 2006).…”
Section: Introductionmentioning
confidence: 99%